2019
DOI: 10.1016/j.lwt.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration properties of gluten-free flours under water addition and shearing conditions

Abstract: Agglomeration properties of gluten-free cereals such as corn, manioc, amaranth, buckwheat, and quinoa flours were investigated. The different states of agglomeration were identified by the evolution of rheological properties under water addition and shearing conditions using a Caleva ® mixer torque rheometer. The Mi-Pro ® highshear granulator has been used to produce wet agglomerates, which were characterized by fraction distribution, water content, density, and agglomeration yield. Results show that all sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results for ash, protein, fat and carbohydrate obtained for the quinoa flour used in this study are in a similar range of the values reported by Navruz-Varli and Sanlier for quinoa grain (2016). When comparing quinoa with the most consumed staples in developing countries, its protein content (14.62%) is higher than that of wheat (13.68%) and rice (6.81%) (Navruz-Varli & Sanlier, 2016), and also than the protein of corn (8.50%), manioc (0.50%) and buckwheat (12.00%) (Chemache et al, 2019). The amount of fiber in the quinoa flour sample is the lowest because the grain already underwent a saponin elimination process that removed its outer layer.…”
Section: Characterization Of the Quinoa Flourmentioning
confidence: 97%
See 1 more Smart Citation
“…The results for ash, protein, fat and carbohydrate obtained for the quinoa flour used in this study are in a similar range of the values reported by Navruz-Varli and Sanlier for quinoa grain (2016). When comparing quinoa with the most consumed staples in developing countries, its protein content (14.62%) is higher than that of wheat (13.68%) and rice (6.81%) (Navruz-Varli & Sanlier, 2016), and also than the protein of corn (8.50%), manioc (0.50%) and buckwheat (12.00%) (Chemache et al, 2019). The amount of fiber in the quinoa flour sample is the lowest because the grain already underwent a saponin elimination process that removed its outer layer.…”
Section: Characterization Of the Quinoa Flourmentioning
confidence: 97%
“…Demir et al (2010) replaced wheat flour with different percentages of chickpea flour and the results showed that a 50% replacement didn't affect the product's sensory and functional properties. More recently, Chemache et al (2019) analyzed the agglomeration properties of manioc, corn, amaranth, buckwheat, and quinoa flours, obtaining positive results for the last four. Jacobsen (2003) suggested that the advantageous properties of quinoa must be exploited through the development of new products and adequate process technologies; to date, its use as a substitute for couscous preparation has not yet been researched.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the FA of food powders as an instant product has mostly focused on dairy-based milk powders [ 7 , 8 , 9 ], fruit and vegetable powders [ 10 , 11 ], and cereal powders [ 5 , 12 ]. Recently, significant research has been conducted on the particle agglomeration of food gums which are widely used in the food industry to improve and control the rheological properties of food products as thickening or gelling agents [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%